Developing the water commons? The (post)political condition and the politics of "shared giving" in Montana. (August 2016) - Anderson, Matthew B.; Ward, Lucas; McEvoy, Jamie; Gilbertz, Susan J.; Hall, Damon M.
Abstract: This paper chronicles the rhetorical mechanisms that fostered a potentially radical re-thinking of water rights and property in a most unlikely place: the libertarian Western U.S., and mobilized by the least likely of actors: state officials. There is growing interest, in geography and beyond, in the question of what constitutes the "properly political" in contexts where dissent is actively forestalled by those with power. Much has been written about the "properly political" as the disruption of the established order by previously excluded actors. Comparatively less research, however, has focused on the "conditions of possibility" that might exist within ostensibly "post-political" governing arenas. This paper deepens our understanding of this by examining a participatory water planning group in Montana, which was convened by the state to develop recommendations for a new state water plan. The group was inspired by an alternative drought-management model called "shared giving." Imbued with principles of "collectivism" and "equality, " the model was strategically (and necessarily) promoted through the discursive shell of the existing prior appropriation system. This was accomplished not by an oppositional force of marginalized actors, but state officials that are rarely, if ever, deemed "disruptive, " and through tactics that are best characterized as post-political. We interpret this case as reflecting a hybrid governing assemblage that highlights both post-political closure and transformative possibilities simultaneously, and conclude by suggesting that the post-political concept, itself, risks foreclosing on conditions whereby fruitful outcomes might become possible from within established governing frameworks otherwise written-off as post-political.